2014
DOI: 10.1055/s-0039-1700322
|View full text |Cite
|
Sign up to set email alerts
|

Clinical assessment of depression and type 2 diabetes in Morocco: Economical and social components

Abstract: Background: The global prevalence of diabetes is increasing worldwide. In Morocco, diabetes and depression are major public health problems, requiring improvement in their care. Diabetes and depression are associated with morbidity and early mortality. This association contributes to raising the risk of the complications that occur, while causing higher suffering to patients, as also an increased cost toward healthcare. Aim: This study aims to assess the prevalence of depression in patients with type 2 diabete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 15 publications
1
5
1
1
Order By: Relevance
“…This was consistent with two of included studies [15,26] and a study conducted in Jazan area [30]. However, other studies contradicted to this finding where the prevalence of depression was found significantly related to the duration of diabetes [31]. This could be attributed to the differences in culture or long experience and adaptation gained in dealing with diabetes complications.…”
Section: Discussionsupporting
confidence: 88%
“…This was consistent with two of included studies [15,26] and a study conducted in Jazan area [30]. However, other studies contradicted to this finding where the prevalence of depression was found significantly related to the duration of diabetes [31]. This could be attributed to the differences in culture or long experience and adaptation gained in dealing with diabetes complications.…”
Section: Discussionsupporting
confidence: 88%
“…In our study among those with poor social support, 51.7% had depression (AOR = 3:68). But the study done in Journal of Diabetes Research 2014 in Morocco indicated that from those who had no social support (security), 43.3% had depression [22]. The higher result in this study may be due to low social support for DM patient in the community, absence of social support in the hospital, and low educational status of the participants to be aware about the disease and its process.…”
Section: Discussionmentioning
confidence: 53%
“…In contrast to our study, several studies in other African countries have shown higher prevalence of depression among T2DM patients. A study in Morocco found that patients with T2DM had higher prevalence of major depression (33.1%) [ 41 ] while studies in South Africa found and in Egypt found 46% and 32% respectively [ 39 ]. Similarly a systematic review conducted in Ethiopia showed that the prevalence of depression among T2DM patients was 39.73% [ 42 ].…”
Section: Discussionmentioning
confidence: 99%